The Influence of Traffic Load on Runway Pavement Condition at Jenderal Ahmad Yani Airport Semarang Using Mechanistic Approach - Noviansyah, Donny Anggara; Sihombing, Atmy Verani Rouly Sihombing (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
The increasing number of passengers and flights at Jenderal Ahmad Yani Airport Semarang is predicted to continue to increase after the Covid-19 pandemic. According to data, the increase that occurred after the pandemic increased by 57% in the period 2021-2023. This increase has the potential to affect the condition of the runway pavement. In 2018, maintenance activities on the runway that have been carried out with the Overlay and Leveling method are planned to maintain pavement conditions until 2038 or 20 years of service life. To anticipate these conditions, flight traffic forecasting is required based on existing conditions until the end of the planning service life. The forecasting results show that the number of passengers can reach 14,369,352 people, which exceeds the planning of only 5,700,000 passengers. With a significant increase in the number of passengers, the results of the evaluation of pavement conditions using the COMFAA and FAARFIELD mechanistic program approaches are represented in the CDF (Cumulative Damage Factor) value. Stating in 2038 the CDF value = 21.25 with a remaining life of 0.9 years. That way the increase that occurs causes significant damage, therefore the rehabilitation process recommended by the FAA is needed with a top layer thickness of 100mm, with implementation carried out in 2026 or when the remaining 5 years of pavement life. Keyword: CDF, Mechanistic, Forecasting, Pavement Life Remaining.